APA Writing Style as a Contributor of Social Knowledge. - McDermott, Christine M.; Meyer, Arial R.; Miller, Monica K. (Information, Medium & Society: Journal of Publishing Studies, 2024)
Publishing the written word is a mode of communicating social knowledge. Publications contribute to social reality when that knowledge is used to educate and make social change. But, not every manuscript will be published; organizations such as the American Psychology Association (APA) set cultural norms that determine which manuscripts become part of social reality. The APA has published seven editions, reflecting how the cultural norms of publishing have shifted over time. This article summarizes guidelines and processes that will help readers from many disciplines publish APA-style works. This article discusses the three major stages of the writing process: preparing to write, writing, and editing. Each section describes the writing norms set by APA as described in the manual and other published sources. By following these cultural norms described here, readers can publish and become part of the cultural and societal process of publishing. In this way, authors using APA writing style contribute to social knowledge.